Dermoscopic evidence of phthirius pubis adjacent to macula cerulea of the back. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2011)
An 8-year-old boy was first observed for intermittent eruption of asymptomatic bluish spots, 1-3 cm in size, lasting a few days, arising from a month on the trunk and on the root of the limbs to a lesser extent. According to his mother, the eruption was preceded by fever and abdominal pain, which suggested vasculitis. The physical examination showed on the back blue spots (Fig. 1), the largest of which, about 3 cm in size, was located on the medial margin of the right scapula (oval). The spots evoked the suspicion of maculae ceruleae. The eyelashes were full of nits (Fig. 4), that did not cause itching and were not noticed by his mother. When putting the dermoscope on the scapular macula cerulea, we saw at a distance of 1 cm from it a self-moving Phthirius (Fig. 2 and 3, arrow), then taken and identified under a microscope (inset of Fig. 3). Removal of nits with vaseline was prescribed.